AKTUALISASI TABIIN PEREMPUAN DALAM PERIWAYATAN HADIS - Junaid bin Junaid (AN-NISA, 2018)
As the second source of Isamic teachings after the Qur’an, the hadith of the prophet Muhammad has provided an accurate understanding of how to comprehend the general contents of the Qur’an. And among those who have made a great contribution to the transmission of hadith is tabiin. tabiins are the third generation after the prophet and the companions. And among the narrations of hadith from among the tabiin, there is also among the women. It can be proved through the actualization of the women in the narration of the hadiths of the prophet well and correctly, thus it will produce a from of actualization that can be accounted for the credibility of the traditions narrated by the women’s tabiin.